Competences, Distinctive Competences, and Core Competences - Eden, C.; Ackermann, Fran (Emerald Group Publishing Limited, 2010)
In order to elaborate the concept of resources (a key component of the well-established resource-based theory of the firm) this paper concentrates on exploring and elaborating the associated concept of competences, in particular distinctive and core competences. This exploration includes an examination of the extant literature, alongside and in parallel with, an extensive body of action research undertaken over 15 years and with 44 top management teams engaged in strategy making. As such the concepts are scrutinized both in terms of their theoretical underpinnings as well as their impact on practice. The research reinforces the view that distinctiveness emerges most powerfully from the identification (or creation) of unique bundles or combinations of competences and that effective and meaningful core competences can be identified from understanding and refining the links between competences and organizational goals. The resultant conceptualization of the systemic competence/ goals structure emerges from the interaction of theory and practice.